2006
DOI: 10.1093/intqhc/mzl039
|View full text |Cite
|
Sign up to set email alerts
|

Culture, language, and patient safety: making the link

Abstract: It has been well recognized internationally that hospitals are not as safe as they should be. In order to redress this situation, health care services around the world have turned their attention to strategically implementing robust patient safety and quality care programmes to identify circumstances that put patients at risk of harm and then acting to prevent or control those risks. Despite the progress that has been made in improving hospital safety in recent years, there is emerging evidence that patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 17 publications
2
122
0
4
Order By: Relevance
“…[8][9][10] In Australia, barriers to care for migrants were formally acknowledged in the early 1970s 11 prompting the establishment of two nationally funded programs -the Health Care Interpreter Service and the Ethnic Health Worker programdesigned to ameliorate some key factors impeding care.…”
Section: Australian Health Review May 2008 Vol 32 No 2 237mentioning
confidence: 99%
“…[8][9][10] In Australia, barriers to care for migrants were formally acknowledged in the early 1970s 11 prompting the establishment of two nationally funded programs -the Health Care Interpreter Service and the Ethnic Health Worker programdesigned to ameliorate some key factors impeding care.…”
Section: Australian Health Review May 2008 Vol 32 No 2 237mentioning
confidence: 99%
“…In one study, communication problems contributed to adverse events at a much higher rate among LEP patients (52.4%) than English speakers (35.9%), with 49.1% of adverse events rising to the level of clinical significance in LEP populations, compared to 29.5% in English-speaking populations. 3 Many studies have shown that LEP patients tend to have lower rates of preventive screening and higher rates of hospitalization and drug complications 2,3,9,[11][12][13][14][15] . Lack of discussion and poor understanding of treatment plans, including medication side effects, are likely reasons for these concerning rates, as such factors can lead to patient dissatisfaction and reduce adherence to physician recommendations [16][17][18] .…”
mentioning
confidence: 99%
“…Un accès limité aux services de santé en français, situation rapportée par plus de la moitié des francophones en situation linguistique minoritaire (FCFA, 2001), constitue une barrière ayant des effets négatifs sur les résultats des traitements et la satisfaction des patients (Forgues, Doucet et Guignard Noël, 2011). On constate que la capacité de communiquer dans sa langue avec les professionnels de la santé encourage l'usage de mesures préventives et peut favoriser la justesse des diagnostics et l'observation des consignes (Bowen, 2001 ;Johnstone et Kanitsaki, 2006 ;Manson, 1988 ;Woloshin, Schwartz, Katz et Welsh, 1997). De plus, une bonne communication assure le respect de la confidentialité du patient et l'obtention adéquate d'un consentement aux soins (Bowen, 2001).…”
Section: Les Besoins De Santé Des Francophones En Situation Minoritaireunclassified